Leptin action via LepR-b Tyr(1077) contributes to the control of energy balance and female reproduction - Patterson, Christa M. (Elsevier, 2012)
Leptin action in the brain signals the repletion of adipose energy stores, suppressing feeding and permitting energy expenditure on a variety of processes, including reproduction. Leptin binding to its receptor (LepR-b) promotes the tyrosine phosphorylation of three sites on LepR-b, each of which mediates distinct downstream signals. While the signals mediated by LepR-b Tyr(1138) and Tyr(985) control important aspects of energy homeostasis and LepR-b signal attenuation, respectively, the role of the remaining LepR-b phosphorylation site (Tyr(1077)) in leptin action has not been studied. To examine the function of Tyr(1077), we generated a “knock-in” mouse model expressing LepR-b (F1077), which is mutant for LepR-b Tyr(1077). Mice expressing LepR-b (F1077) demonstrate modestly increased body weight and adiposity. Furthermore, females display impairments in estrous cycling. Our results suggest that signaling by LepR-b Tyr(1077) plays a modest role in the control of metabolism by leptin, and is an important link between body adiposity and the reproductive axis.